Struktur Komunitas Makroalga di Pantai Pandawa, Bali - Anak Agung Raka Triyana Putri; Dewa Ayu Angga Pebriani; Ni Luh Watiniasih (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
Macroalgae are classified as low-level plants (thallophyta), no have vascular and have a vegetative body that has not recognized the differentiation of the roots, stems and leaves, so it is called a thallus. This aims to determine the diversity of macroalgae species and the percentage of maroalgae cover in the waters of Pandawa Beach. The research was conducted for 2 months from January-February 2021. This study used a descriptive method with a quantitative approach. The data were collected at 3 stations using the 1x1 m2 quadrant transect of method. The results of the study found 17 types of macroalgae on Pandawa Beach including Halimeda macroloba, Padina australis, Ulva lactuca, Palmaria palmata, Galaxaura rugosa, Laurencia papillosa, Gracilaria textorii, Turbinaria deccurrens, Halimeda opuntia, Kappaphycus alvarezii, Gracilariopsis longissimi, Chondrococcus hornemannii, Amphiroa fragilissima, Chondrus crispus, Halymenia floresii, Amphiroa rigida, and Phyllophora crispa. The highest abundance value of macroalgae species was Laurencia papillosa species with a total of 2,87 individuals/m2. Based on the results of the calculation of the diversity index value on Pandawa Beach is 1,44-2,02 so it is included in the medium category. The uniformity index value on Pandawa Beach is 0,69-0,87 so it is included in the medium category. The dominance index value on Pandawa Beach is classified as a low category with a value of 0,17-0,28. The highest percentage value of macroalgae cover on Pandawa Beach was Laurencia papillosa with 0,53-2,87%.